ISG15 induction is required during L1-mediated colon cancer progression and metastasis. - Cheriyamundath, Sanith; Basu, Sayon; Haase, Gal; Doernberg, Harry; Gavert, Nancy; Brabletz, Thomas; Ben-Ze'Ev, Avri (Oncotarget, 2019)
Hyperactivation of Wnt/β-catenin target gene expression is a hallmark of colorectal cancer (CRC) development. We identified L1-CAM (L1) and Nr-CAM, members of the immunoglobulin family of nerve cell adhesion receptors, as target genes of the Wnt/β-catenin pathway in CRC cells. L1 overexpression in CRC cells enhances their motile and tumorigenic capacity and promotes liver metastasis. L1 is often localized at the invasive edge of CRC tissue. Using gene arrays and proteomic analyses we identified downstream signaling pathways and targets of L1-mediated signaling. Here, we found that the expression of interferon-stimulated gene 15 (ISG15) that operates much like ubiquitin (is conjugated to proteins by ISGylation), is elevated in the conditioned medium and in CRC cells overexpressing L1. Suppression of endogenous ISG15 levels in L1-expressing cells blocked the increased proliferative, motile, tumorigenic and liver metastatic capacities of CRC cells. ISG15 overexpression, on its own, could enhance these properties in CRC cells, but only to a much lower extent compared to L1. We show that NF-κB signaling is involved in the L1-mediated increase in ISG15, since blocking the NF-κB pathway abolished the induction of ISG15 by L1. Point mutations in the L1 ectodomain that interfere with its binding to L1 ligands, also inhibited the increase in ISG15. We detected high levels of ISG15 in human CRC tissue cells and in the adjacent stroma, but not in the normal mucosa. The results suggest that ISG15 is involved in L1-mediated CRC development and is a potential target for CRC therapy.
EVALuna2:384412